Individuals with greater science literacy and education have more polarized beliefs on controversial science topics - Drummond, Caitlin (Proc Natl Acad Sci U S A, 2017)
Although Americans generally hold science in high regard and respect its findings, for some contested issues, such as the existence of anthropogenic climate change, public opinion is polarized along religious and political lines. We ask whether individuals with more general education and greater science knowledge, measured in terms of science education and science literacy, display more (or less) polarized beliefs on several such issues. We report secondary analyses of a nationally representative dataset (the General Social Survey), examining the predictors of beliefs regarding six potentially controversial issues. We find that beliefs are correlated with both political and religious identity for stem cell research, the Big Bang, and human evolution, and with political identity alone on climate change. Individuals with greater education, science education, and science literacy display more polarized beliefs on these issues. We find little evidence of political or religious polarization regarding nanotechnology and genetically modified foods. On all six topics, people who trust the scientific enterprise more are also more likely to accept its findings. We discuss the causal mechanisms that might underlie the correlation between education and identity-based polarization.